2021
DOI: 10.1002/celc.202100790
|View full text |Cite
|
Sign up to set email alerts
|

NO Electroreduction by Transition Metal Dichalcogenides with Chalcogen Vacancies

Abstract: Nitric oxide electroreduction reaction (NOER) is one of the most attractive routes for ammonia synthesis and NOx‐related pollutant treatment. However, current research on NOER catalysts mainly focus on noble metals and single atom catalysts, while low‐cost transition metal dichalcogenides (TMDs) are rarely considered, let alone their product selectivity. Herein, using first‐principles calculations, we systematically investigate the performance of a series of single‐layer TMDs (MoS2, MoSe2, MoTe2, TaTe2 and WTe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 92 publications
1
18
0
Order By: Relevance
“…Furthermore, iron(II) sodium benzoate (Fe II SB) was added to the electrolyte as an absorber to attract more NO to the catalyst surface. Theoretical work suggested that single-layer TMDs with chalcogen vacancies (such as defective 1T'-MoS2 and 1T'-MoSe2) may serve as efficient NORR catalysts for NH3 synthesis [364]. We used plasma etching to create varying S-vacancy contents from hydrothermally prepared CoS precursors [365].…”
Section: Metal-n2 Based Batteriesmentioning
confidence: 99%
“…Furthermore, iron(II) sodium benzoate (Fe II SB) was added to the electrolyte as an absorber to attract more NO to the catalyst surface. Theoretical work suggested that single-layer TMDs with chalcogen vacancies (such as defective 1T'-MoS2 and 1T'-MoSe2) may serve as efficient NORR catalysts for NH3 synthesis [364]. We used plasma etching to create varying S-vacancy contents from hydrothermally prepared CoS precursors [365].…”
Section: Metal-n2 Based Batteriesmentioning
confidence: 99%
“…Here, NO → HNO* is the potential limiting step with the U L of −0.19 V for the pristine MSN monolayer. Compared with other reported NOER catalysts, 4,49,50 the pristine MSN monolayer is not the optimal catalyst due to the weak NO adsorption on the MSN monolayer.…”
Section: Resultsmentioning
confidence: 76%
“…3 The direct NO electrochemical reduction reaction (NOER) is an environmentally friendly strategy for eliminating NO. 4,5 Furthermore, the main product of NOER is ammonia (NH 3 ), which can be used as not only a biofuel to provide energy, but also the raw material for the production of chemical fertilizers, pharmaceuticals, rubber and other materials. 6 Noble metals such as Pt, Pd, Ir and Au are usually employed as the NOER electrocatalysts, however, they are hindered by low atomic efficiencies and high costs.…”
Section: Introductionmentioning
confidence: 99%
“…17,20,24−29 Notably, transition-metal dichalcogenides (TMDs) exhibit admirable electrocatalytic power toward producing NH 3 by NORR. 17,25,30 Our recent work also demonstrated the direct use of a MoS 2 nanoarray for electrochemically converting NO into NH 3 . 17 As a typical TMD, cobalt sulfide has attracted wide research attention for application in catalysis, 31 batteries, 32 and supercapacitors.…”
Section: ■ Introductionmentioning
confidence: 85%
“…Noble metal-based electrocatalysts have been proved to have catalytic activity in NORR, but their high cost and scarcity make them difficult for large-scale applications. Research interest has thus shifted to earth-abundant NORR electrocatalysts. ,, Notably, transition-metal dichalcogenides (TMDs) exhibit admirable electrocatalytic power toward producing NH 3 by NORR. ,, Our recent work also demonstrated the direct use of a MoS 2 nanoarray for electrochemically converting NO into NH 3 . As a typical TMD, cobalt sulfide has attracted wide research attention for application in catalysis, batteries, and supercapacitors .…”
Section: Introductionmentioning
confidence: 99%